2021
DOI: 10.1055/a-1345-7890
|View full text |Cite
|
Sign up to set email alerts
|

Growth Promotion and Increased ATP-Binding Cassette Transporters Expression by Liraglutide in Triple Negative Breast Cancer Cell Line MDA-MB-231

Abstract: Background Glucagon-like petide-1 (GLP-1) agonists such as liraglutide are widely employed in type 2 diabetes due to their glucose reducing properties and small risk of hypoglycemia. Recently, it has been shown that GLP-1agonists can inhibit breast cancer cells growth. Nonetheless, concerns are remained about liraglutide tumor promoting effects as stated by population studies. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In the human estrogen receptorpositive MCF7 breast cancer cell line, GLP-1RA have consistently been reported to have anti-proliferative and pro-apoptotic effects (50)(51)(52)(53). In contrast, in the MDA-MB-231 TNBC cell line, the GLP1-RA liraglutide was found to stimulate cell growth in vitro, but exendin-4 reduced the proliferation (53)(54)(55). In vivo, liraglutide was also reported to accelerate the growth of murine 4T1 cells in a syngeneic model (55), but exendin-4 inhibited the growth of MDA-MB-231 and MDA-MB-468 TNBC xenografts (53).…”
Section: Discussionmentioning
confidence: 99%
“…In the human estrogen receptorpositive MCF7 breast cancer cell line, GLP-1RA have consistently been reported to have anti-proliferative and pro-apoptotic effects (50)(51)(52)(53). In contrast, in the MDA-MB-231 TNBC cell line, the GLP1-RA liraglutide was found to stimulate cell growth in vitro, but exendin-4 reduced the proliferation (53)(54)(55). In vivo, liraglutide was also reported to accelerate the growth of murine 4T1 cells in a syngeneic model (55), but exendin-4 inhibited the growth of MDA-MB-231 and MDA-MB-468 TNBC xenografts (53).…”
Section: Discussionmentioning
confidence: 99%
“…43 According to another study, depending on the cell population concentration, liraglutide could be both a stimulator and an inhibitor of MDA-MB-231 cell proliferation. 44 Moreover, researchers have indicated that DPP-4 signaling can promote epidermal growth factor-induced epithelial cell transformation and mammary tumorigenesis via the induction of peptidylpropyl cis-trans isomerase 1 expression, suggesting that sitagliptin as a DPP-4I could be useful for the treatment of breast tumors in patients with T2DM. 45 On the contrary, cell lines analysis suggested that DPP-4 inhibition could accelerate BC metastasis by inducing epithelial-mesenchymal transition through C-X-C motif chemokine 12/C-X-C receptor4 (CXCL12/CXCR4)mediated mammalian target of rapamycin activation and promote chemoresistance in BC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Liraglutide restricted the expression of microRNA 27a and in turn promoted the expression of the AMPKα2 protein in MCF-7 cells [ 199 ]. However, this agent promoted the proliferation of highly invasive MDA-MB-231 cells which possessed AMPK-dependent EMT properties [ 200 ]. Alteration of the ATP/AMP ratio is a common mechanism that some modulators apply to activate AMPK [ 201 ].…”
Section: Potential Ampk Modulators Of Chemical Synthesismentioning
confidence: 99%